National practice of Nursing professionals in the insertion of peripheral vascular access devices - Bianka Sousa Martins Silva; Luciano Marques dos Santos; Patrícia Kuerten Rocha; Aline Nair Biaggio Mota; Ariane Ferreira Machado Avelar; Denise Miyuki Kusahara (Universidade de São Paulo, 2024)
Objective: to identify and compare the practice of Nursing professionals regarding the insertion of peripheral vascular access devices, according to professional category. Method: descriptive sectional study carried out between July 2021 and May 2022 with 2,584 Nursing professionals, using a questionnaire validated by three judges with expertise in intravenous therapy, containing variables related to catheterization and the vascular access device. Descriptive and inferential analysis was carried out. Results: most professionals do not prepare the patient or perform some essential care before attempting peripheral intravenous catheterization. Regarding the preferred catheterization site, hands, arm and forearm stand out. There is no control over the tourniquet time, and the patient is punctured more than three times. The most used device materials are polyurethane and Teflon ® , more than one criterion is adopted for device selection, and Micropore ® type adhesive tape was the covering most cited by Nursing professionals. The identification of catheterization was not adequate. Conclusion: Nursing technicians and assistants are the professionals who least comply with what is recommended in recognized guidelines. Nurses' practice also presents deviations from scientific evidence.